Premiia . The Bonus - Mikaelyan, Sergei (Lenfilm, 1974)
Duration: 01:24:00 In this officially recognized film, which won the State Prize of the Soviet Union, the inadequacies of the Soviet system are to a certain degree acknowledged. This alone provoked some interest in the film at the time of its release, in 1975. Based on the very popular and prize-winning play by Aleksandr Gelman, it tells the story of a group of factory workers, led by Potapov, (Yevgeny Leonov ) who uncharacteristically refuse to accept a pay bonus because it is clearly in error. They know this because the entire factory has consistently been run in a slipshod manner.